PENGEMBANGAN TES HIGHER ORDER THINKING SKILLS (HOTS) MATERI GERAK LURUS BERUBAH BERATURAN UNTUK SMA - Afriani, Erika; Maria S, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to developed the Higher Order Thinking Skills (HOTS) test of motion topics for Senior High School students. The method in this research was developed from Borg and Gall development model which har been simplified into 7 steps, that werw colecting data, planning, designing product, testing in a small scale, revisi, testing in a large scale and revisi final product. The test consists of 22 multiple choisce questions. The test involved 33 studens in small-scale trials and 194 students on large-scale trials. Based on date analyze, HOTS test developed is proper to used which test caracteristic of high validity level, high reability, easy to moderate level of difficullty and readability index greater or equal to 6. The analysis results of contens validity is 0.75, result of item validity is 16 question valid, and result of construct validity has a high levelof item correlation. The reability of this test was 0.607 and readability index of this test was 8.65. So, there werw 15 of 22 developed question that could be used.Keywords: Development of Higher Order Thinking Skills (HOTS), Test Characteristics, Accelerated Linear Motion